Contract Law and Its Impact on Indonesian Contract Law - Rahman, Arif; Topon, Yunita Irianti; Purbawati, Retno; Mumtaza, Fielsa Kabida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
International commercial contracts are contracts that are concluded by parties who come from different countries or are subject to different legal systems. Because the provisions in the contract can be interpreted differently by the parties, such a contract must contain provisions regarding dispute resolution which also includes a choice of law or a choice of dispute resolution forum. Another available means of preventing disputes and conflicts of law from international commercial contracts is through the harmonization of States' national contract laws. Indonesia as an active member of the international commercial community must immediately take initiatives for that. In other words, Indonesian contract law must be revised immediately